In-situ surface passivation induced by short-chain PFAS transformation products suppresses electrochemical degradation of microplastics - Shengping Yang; Yuehua Zhang; Xianfang Fan; Mengjuan Yao; Yuanji Shi; Linyan Yang; Xueming Chen (Chemical Engineering Journal, 2026)

Rapid detection of porcine circovirus type2 using a combination of RAA isothermal amplification and Cas12a nucleic detection technology - Lejia Fan; Xueming Liu; Jiaqing Hu; Jinjin Chi; Xiaoyu Fei; Chao Qi; Enhui Wang; Feng Su (Research in Veterinary Science, 2026)

From radical/electron competition to interfacial shielding: How PFOA and its derivatives obstruct electrochemical degradation of microplastics - Yuehua Zhang; Shengping Yang; Yinghui Lin; Xianfang Fan; Mengjuan Yao; Shihua Yin; Yuanji Shi; Linyan Yang; Zhijie Chen; Bing-Jie Ni; Xueming Chen (Journal of Hazardous Materials, 2026)

Unveiling sulfur-vacancy-induced electron transfer pathways in FeNi2S4 steering peroxydisulfate activation from radical to non-radical oxidation - Yuansheng Wang; Xueming Lin; Zhicong Lan; Jiayi Li; Honghao Zeng; Hanyun Zhang; Min Yu; Jiaqu Tan; Dongya Li; Fan Yang (Chemical Engineering Journal, 2026)

Effect of high-intensity pulsed magnetic field on protein-starch interactions and quality of fresh noodles - Fan Liu; Zhuoying Wang; Na Yang; Yamei Jin; Xueming Xu (Innovative Food Science & Emerging Technologies, 2026)

Substituting straw with biochar enhances rice production and net economic benefit while reducing the carbon footprint in a double-cropping rice system - Shiqi Yang; Yanghaojun Xu; Wenyang Kuang; Wenhao Fan; Xueming Tan; Xiaohua Pan; Yanhua Zeng (Field Crops Research, 2026)

High-intensity pulse magnetic field treatment of cubilose gel and its response signal analysis - Fuchao Shi; Fan Liu; Yamei Jin; Jianmei Lian; Hongming Li; Na Yang; Xueming Xu; Bimal Chitrakar (Food Hydrocolloids, 2026)

Flexural performance of UHPC-encased H-shape steel beams: Experiments and theoretical analysis - Yuquan Ma; Feng Jiang; Zefeng Ou; Kuanghuai Wu; Xueming Fan; Yi Shao (Engineering Structures, 2026)

Multiphysics synergistic thawing technologies for mitigating meat quality deterioration: Mechanisms, applications, and future perspectives - Huangbing Yao; Ankun Zhang; Fan Liu; Yamei Jin; Lingtao Zhang; Guoqiang Shao; Na Yang; Xueming Xu (Food Research International, 2025)

Effects of static magnetic fields on the physicochemical and flavor quality of strawberry fruit during cold storage - Fan Liu; Xiaoyue Mo; Sijian Zhou; Jian Wei; Na Yang; Yamei Jin; Xueming Xu (Food Chemistry, 2025)

Kinetics study on microbial growth and surfactin production of Bacillus subtilis ATCC 21332 under the synergistic effect of magnetic field and Mg2+ - Sirui Chen; Fuchao Shi; Fan Liu; Na Yang; Xueming Xu; Yamei Jin (Food Bioscience, 2025)

Unraveling the intrinsic mechanism of recyclable octahedral Fe3S4-triggered peroxydisulfate activation for contaminant degradation: The pivotal role of high-valent iron-oxo species - Jiaqu Tan; Zhuoxun Tian; Fengjie Qin; Qiaojuan Kong; Dongya Li; Fan Yang; Zhen Zhang; Yulong Zhang; Yongtao Li; Xueming Lin (Chemical Engineering Journal, 2024)

Effects of sourdough on bread staling rate: From the perspective of starch retrogradation and gluten depolymerization - Meixuan Li; Honghong Zhang; Lingyi Lyu; Qing Deng; Haoran Fan; Xueming Xu; Dan Xu (Food Bioscience, 2024)

Insight into the interaction mechanism between mulberry polyphenols and β-lactoglobulin - Qi Yuan; Lin He; Xuping Wang; Huaigu Yang; Fan Zhu; Xiaoxia Peng; Jingrong Cheng; Yaosheng Lin; Daobang Tang; Xueming Liu (Food Hydrocolloids, 2024)

Deterioration mechanisms and quality improvement methods in frozen dough: An updated review - Honghong Zhang; Haoran Fan; Xueming Xu; Dan Xu (Trends in Food Science & Technology, 2024)

High capillary effect and solar dual-drive nanofibrillated cellulose aerogels for efficient crude oil spill cleanup - Bingjie Fan; Xueming Bao; Shanshan Pan; Ying Liu; Yuanyuan Yu; Li Cui; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Pilot test of high-pressure water jet slotting with liquid CO2 injection to displace CH4 and improve coal seam permeability - Wansheng Mi; Hu Wen; Shixing Fan; Gaoming Wei; Mingyang Liu; Shibin Wang; Haihong He; Xueming Wu; Xiaojiao Cheng; Bocong Liu; Rijun Li (Fuel, 2023)

Effects of mulberry pomace polysaccharide addition before fermentation on quality characteristics of yogurt - Huaxin Du; Xuping Wang; Huaigu Yang; Fan Zhu; Jingrong Cheng; Xiaoxia Peng; Yaosheng Lin; Xueming Liu (Food Control, 2023)

Effect of sourdough on the quality of whole wheat fresh noodles fermented with exopolysaccharide lactic acid bacteria - Yake Du; Zhen Dai; Tingting Hong; Qing Bi; Haoran Fan; Xueming Xu; Dan Xu (Food Research International, 2023)

Extending shelf life of fresh noodles with nisin producer Lactococcus lactis subsp. lactis fermented sourdough and characteristic changes during storage - Anying Nie; Xuepan Qi; Tingting Hong; Yamei Jin; Haoran Fan; Xueming Xu; Dan Xu (Food Control, 2023)

N-doped biochar mediated peroxydisulfate activation for selective degradation of bisphenol A: The key role of potential difference-driven electron transfer mechanism - Jiaqu Tan; Xinmin Chen; Mengru Shang; Jiannan Cui; Dongya Li; Fan Yang; Zhen Zhang; Haotian Zhang; Qitang Wu; Yongtao Li; Xueming Lin (Chemical Engineering Journal, 2023)

Human Cytomegalovirus IE2 Disrupts Neural Progenitor Development and Induces Microcephaly in Transgenic Mouse - Delei Niu; Xianjuan Zhang; Shuyun Zhang; Tianyu Fan; Xiaoqiong Zhou; Hui Wang; Xueming Zhang; Fulong Nan; Shasha Jiang; Fengjun Liu; Yunyang Wang; Bin Wang (Molecular Neurobiology, 2023)
Human cytomegalovirus (HCMV) is a significant contributor to congenital birth defects. Limited by the lack of animal models, the pathogenesis of neurological damage in vivo caused by HCMV infection and the role of individual viral genes remain to be elucidated. Immediate early (IE2) protein may play a function in neurodevelopmental problems caused by HCMV infection. Here, this study intended to investigate IE2’s long-term effects on development of the brain in IE2-expressing transgenic mice (Rosa26-LSL-IE2 +/− , Camk2α-Cre) aimed to observe the phenotype of postnatal mice. The expression of IE2 in transgenic mice was confirmed by PCR and Western blot technology. We collected mouse brain tissue at 2, 4, 6, 8, and 10 days postpartum to analyze the developmental process of neural stem cells by immunofluorescence. We discovered that transgenic mice (Rosa26-LSL-IE2 +/− , Camk2α-Cre) can reliably produce IE2 in the brain at various postpartum phases. Furthermore, we also observed the symptoms of microcephaly in postnatal transgenic mice, and IE2 can damage the amount of neural stem cells, prevent them from proliferating and differentiating, and activate microglia and astrocytes, creating an unbalanced environment in the brain’s neurons. In conclusion, we demonstrate that long-term expression of HCMV-IE2 can cause microcephaly through molecular mechanisms affecting the differentiation and development of neural stem cells in vivo. This work establishes a theoretical and experimental foundation for elucidating the molecular mechanism of fetal microcephaly brought by HCMV infection in throughout the period of neural development of pregnancy. Graphical Abstract

Effect of weak magnetic field on the water-holding properties, texture, and volatile compounds of pork and beef during frozen storage - Fan Liu; Na Yang; Lingtao Zhang; Yamei Jin; Zhengyu Jin; Xueming Xu (Food Bioscience, 2023)

Magnetic field delays the senescence of strawberries by maintaining energy state and regulating respiratory metabolism - Fan Liu; Na Yang; Lingtao Zhang; Bo Cui; Yamei Jin; Zhengyu Jin; Xueming Xu (Postharvest Biology and Technology, 2023)

Genome-wide analysis of genetic pleiotropy and causal genes across three age-related ocular disorders - Xueming Yao; Hongxi Yang; Han Han; Xuejing Kou; Yuhan Jiang; Menghan Luo; Yao Zhou; Jianhua Wang; Xutong Fan; Xiaohong Wang; Mulin Jun Li; Hua Yan (Human Genetics, 2023)

Regulation on the quality of yogurt by phenolic fraction of mulberry pomace supplemented before and after fermentation - Huaxin Du; Xuping Wang; Huaigu Yang; Fan Zhu; Jie Liu; Jingrong Cheng; Yaosheng Lin; Daobang Tang; Xueming Liu (Food Control, 2023)

RNA-seq Provides Novel Insights into Response to Acute Salinity Stress in Oriental River Prawn Macrobrachium nipponense - Yaoran Fan; Jianbin Feng; Nan Xie; Feiyue Ling; Zefei Wang; Keyi Ma; Xueming Hua; Jiale Li (Marine Biotechnology, 2022)

Upregulation of HRD1 promotes cell migration and invasion in colon cancer - Xueming Tan; Xiaolu He; Zhining Fan (Molecular and Cellular Biochemistry, 2019)

Soil N/P and C/P ratio regulate the responses of soil microbial community composition and enzyme activities in a long-term nitrogen loaded Chinese fir forest - Fangfang Shen; Jianping Wu; Houbao Fan; Wenfei Liu; Xiaomin Guo; Honglang Duan; Liang Hu; Xueming Lei; Xiaohua Wei (Plant and Soil, 2019)

Dynamic changes of histone H3 lysine 9 following trimethylation in bovine oocytes and pre-implantation embryos - Sheng Zhang; Fang Wang; Congli Fan; Bo Tang; Xueming Zhang; Ziyi Li (Biotechnology Letters, 2016)

Derlin-1 is overexpressed in human colon cancer and promotes cancer cell proliferation - Xueming Tan; Xiaolu He; Zhonghua Jiang; Xiaohong Wang; Limei Ma; Li Liu; Xiang Wang; Zhining Fan; Dongming Su (Molecular and Cellular Biochemistry, 2015)

Effects of WT1 gene downregulation on apoptosis in porcine fetal fibroblasts - Peipei An; Yu Ding; Aibing Wang; Wentao Tan; Fei Gao; Anran Fan; Bo Tang; Xueming Zhang; Ziyi Li (In Vitro Cellular & Developmental Biology - Animal, 2014)

miRNAs promote generation of porcine-induced pluripotent stem cells - Kuiying Ma; Guangqi Song; Xinglan An; Anran Fan; Wentao Tan; Bo Tang; Xueming Zhang; Ziyi Li (Molecular and Cellular Biochemistry, 2014)

Effects of tillage management on infiltration and preferential flow in a black soil, Northeast China - Ruqin Fan; Xiaoping Zhang; Xueming Yang; Aizhen Liang; Shuxia Jia; Xuewen Chen (Chinese Geographical Science, 2013)